Transcriptional regulation of the endogenous danger signal tenascin-C: a novel autocrine loop in inflammation. - Goh, F; Piccinini, A; Krausgruber, T; Udalova, I; Midwood, K (2010)
Inappropriate expression of proinflammatory mediators underpins the pathogenesis of autoimmune disease and tumor metastasis. The extracellular matrix glycoprotein tenascin-C is an endogenous activator of innate immunity that promotes the synthesis of inflammatory cytokines via activation of TLR4. Little tenascin-C is observed in most healthy adult tissues, but expression is specifically upregulated at sites of inflammation. Moreover, high levels of tenascin-C are associated with chronic inflammation and found in the tumor stroma. In this study, we show that the expression of tenascin-C is induced in immune myeloid cells activated by a variety of inflammatory stimuli, including specific TLR ligands. Its synthesis is transcriptionally regulated and requires the specific activation of AKT/PI3K and NF-kappaB signaling pathways. Using a bioinformatic approach, we identified a large number of conserved noncoding regions throughout the tenascin-C genomic locus that may contribute to its transcriptional regulation during inflammation. We also demonstrate that tenascin-C expression is transient during acute inflammation. In contrast, persistently high levels of expression occur in the inflamed synovium of joints from rheumatoid arthritis patients. Thus, misregulated expression of this endogenous danger signal may promote an autocrine loop of inflammation and contribute to the persistence of inflammation in autoimmune diseases or to tumor egress and invasion during metastasis.